Integrated design of photovoltaic power generation plant with pumped hydro storage system and agricultural facilities in Uhuelem-Amoncha African community - ONU, Uchenna Godswill (2022)
Seasonal and location dependence of renewable energy resources have limited their applications in power generation. Energy storage systems are promising solutions to the intermittence of renewable energy resources. Rural electricity grids are faced with economic sustainability challenges due to low power demand and poverty. As countries hopefully pass through various stages of development, their needs change. The electricity needs of developing countries surely differ from those of developed economies. Most of the global population without access to electricity, and all the consequences of it, is found in developing countries. Energy access is undoubtedly a significant catalyst for development. Developed countries mainly require technologies to ensure energy security, resilience, and occasionally emission control. Therefore, microgrids are emerging technologies capable of supporting the diverse needs of various stages of development. For example, a rural grid design around economic drivers like agriculture and micro industries can mitigate poverty and improve economic sustainability of rural grids. This study presents an Integrated Design of Photovoltaic Power Generation Plant with Pumped Hydro Storage System and Agricultural Facilities in Uhuelem-Amoncha African Community. The design explored the natural availability of water body in an elevated settlement area that offers a natural storage height for hydro energy storage. HOMER (Hybrid Optimization of Multiple Energy Resources) software was deployed to optimize the design. The designed photovoltaic power generation plant has a nominal capacity of 221 kW. The simulated results show the power supply probability of the plant as 99.9%. The cost of energy (COE) offered by the design is 0.456 [US$/kWh] which is 82% lower than the current cost of energy in the project community based on generation through petrol generators. The System has 100% renewable energy penetration. The plant is designed to power 50 households with a daily domestic energy consumption of 4.46 [kWh] each. The plant capacity also covers the irrigation water requirement of 50 acres of corn farms. A total of 100 units of designed intelligent pest control system will also be powered by the plant. A community refrigeration scheme of 27 [m3] equivalent volume is part of the plant design load. The benefits from the irrigation, water supply, pest control and refrigeration scheme will enhance the community’s socio-economic development and sustain the investment. Quantifying the integral socio-economic and environmental benefits is a subject of a future research.